2016
DOI: 10.1080/14634988.2016.1145027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of four wetland plants on nutrient removal and growth of eutrophic algae

Abstract: We studied the removal of chlorophyll-a and eutrophic alga Ankistrodesmus acicularis by mixed and monoculture constructed wetlands of four common wetland macrophytes, Echinodorus berteroi, Hydrocotyle sibthorpioides, Vallisneria natans and Hydrilla verticillata. We also tested the effects of the macrophyte culture solution on the growth of three common eutrophic algae: Chlorella pyrenoidosa, Scnedesmus obliquus and Anabaena flosaquae. The wetlands had significant effect on the removal of chlorop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…It has been confirmed that aquatic macrophytes can inhibit the growth of algae and control algal bloom [52]. The inhibitory effect may be related to competition for nutrients, light and other resources with algae [52,53]. An earlier study reported that CW had a stable reduction percentage for Chla (58 to 73%) in aquaculture pond water [10].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It has been confirmed that aquatic macrophytes can inhibit the growth of algae and control algal bloom [52]. The inhibitory effect may be related to competition for nutrients, light and other resources with algae [52,53]. An earlier study reported that CW had a stable reduction percentage for Chla (58 to 73%) in aquaculture pond water [10].…”
Section: Discussionmentioning
confidence: 95%
“…Excessive phytoplankton, especially cyanobacteria, can cause poor water quality and have negative effects on fish and shrimps in ponds [51]. It has been confirmed that aquatic macrophytes can inhibit the growth of algae and control algal bloom [52]. The inhibitory effect may be related to competition for nutrients, light and other resources with algae [52,53].…”
Section: Discussionmentioning
confidence: 99%